Reconstruction of partial maxillectomy defect with a buccal fat pad flap and application of 4-hexylresorcinol: a case report - Seok, Hyun (J Korean Assoc Oral Maxillofac Surg, 2016)
Mucoepidermoid carcinoma (MEC) is the most common type of malignant neoplasm in the minor salivary gland. The hard palate is a frequently involved site of MEC. The treatment of low-grade MEC on the hard palate is wide local resection with a tumor-free margin. In the present case, the maxillary defect was reconstructed using a buccal fat pad (BFP) flap, followed by application of 4-hexylresorcinol (4HR) ointment for 2 weeks. The grafted BFP successfully covered the tumor resection defect without tension and demonstrated complete re-epithelialization without any complications.